2007
DOI: 10.1007/s11224-007-9165-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic simulation of sub- and supercritical water with new interaction potential

Abstract: Molecular dynamic simulation of water under sub-and supercritical conditions was performed with a new form of OÁÁÁH pairwise potential with an additional nonelectrostatic term corresponding hydrogen bond formation. Some structural properties of water and hydrogen bonds characteristics were calculated in a wide temperature range and pressure 50 MPa. Dependences of these values on temperature were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, changes in the dielectric constant of water from ambient to SC conditions make it an excellent solvent for many organic compounds. [3][4][5] Several experimental [6][7][8][9][10][11] and computer simulation (using different molecular models for water) [12][13][14][15][16][17][18][19][20] studies on the structural properties of supercritical water have shown that the hydrogen bonds are still present even at elevated temperatures. With increasing temperature or decreasing density the tetrahedral ordering of the water molecules present under ambient conditions is broken and a substantial amount of hydrogen bonds between water molecules are disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes in the dielectric constant of water from ambient to SC conditions make it an excellent solvent for many organic compounds. [3][4][5] Several experimental [6][7][8][9][10][11] and computer simulation (using different molecular models for water) [12][13][14][15][16][17][18][19][20] studies on the structural properties of supercritical water have shown that the hydrogen bonds are still present even at elevated temperatures. With increasing temperature or decreasing density the tetrahedral ordering of the water molecules present under ambient conditions is broken and a substantial amount of hydrogen bonds between water molecules are disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…Being interested in various subjects he invited to the conferences specialists working in different fields, and reports and numerous discussions with participants stimulated new themes in his investigations. So, it is quite natural that the most part of papers in this issue devoted both organic crystal chemistry [107][108][109] and structural investigations of other objects [102,[110][111][112] are presented by regular participants of these conferences.…”
mentioning
confidence: 99%
“…Petrenko et al [224] reported on molecular dynamic simulation of water under sub-and supercritical conditions. Sub-and supercritical water are unique phases [225].…”
Section: Issuementioning
confidence: 99%